Adaptive Reuse of Historic Buildings for Museum Purposes: A Comprehensive Analytical Framework - BUABAI, TIRA (International Journal of Building, Urban, Interior and Landscape Technology, 2025)
This research explores the conversion of historical buildings into museums, focusing on their original roles and architectural characteristics. This qualitative study employs a comparative analysis of selected adaptive-reuse museum cases across Southeast Asia and an extensive literature review to examine how original building typologies, spatial organization, ethical considerations, and community engagement shape museum outcomes. It examines case studies from Southeast Asia, such as Thailand, Malaysia, and Singapore, and how these buildings influence exhibition planning, spatial structuring, and public engagement. The study views reuse as a flexible strategy that connects with broader economic, social, and environmental issues. Economically, modifying existing structures is often more cost-effective than building new ones, reducing material costs, opening avenues for heritage tourism, and accessing diverse funding sources. Socially, it promotes cultural continuity, stimulates inclusivity, and strengthens relationships between institutions and communities. Environmentally, reuse fosters sustainable development by preserving embedded energy in existing materials, reducing construction waste, and aligning with climate-responsive design concepts. The research also addresses ethical issues, emphasizing the responsibility of carefully interpreting history, ensuring equal access, and maintaining transparency in funding and operational processes. It also addresses challenges such as integrating modern facilities without compromising heritage values, responding to safety and accessibility requirements, and engaging stakeholders at every stage. The study concludes that if guided by thoughtful design and collective conservation, repurposing historic buildings will be a more modern, culturally rooted, and sustainable choice than new construction.